Determining the English language needs of Diploma in Creative Technology (THEATRE) students / Turisiana Ahmad Buhari and Fauziah Saadah Abdul Halim - Ahmad Buhari, Turisiana; Abdul Halim, Fauziah Saadah (Research Management Institute (RMI), 2010)
This study was designed to determine the English language needs of Diploma in Creative Technology (Theatre) students. A sample of 98 students participated in this study. It was revealed that speaking and reading skills are the two most important English language skills the students need to have in the Theatre programme. In addition, these two skills are the skills that Theatre students need to practice even more. Furthermore, it was discovered that Theatre students would prefer to learn English language speaking skills more compared to other skills.